Revival Movements as Conflict Agendas of the Popular in the Nineteenth and Early Twentieth Centuries
XVII, 277 p. 27 illus.
Keywords: ‘This intriguing volume offers a significant contribution to the growing field of lived religion, i.e. religion from the perspective of laymen and women, who sought empowerment through their faith. The volume not only provides readers with much new knowledge about religious revival movements; the geographical breadth of the chapters offers new opportunities to explore the topic from a sociological and trans-denominational perspective. Anyone with an interest in global history, social history, and gender studies will have an interest in this work.’ - Juliane Engelhardt, University of Copenhagen, Denmark ‘This is a significant contribution to the historiography of revival movements in the long nineteenth century. Ranging from Russia and Finland to India and the US, the chapters highlight the international and cross-denominational dynamics of Protestant awakenings and how they intersected with diverse esoteric revivals. Especially rewarding is the focus on formations of popular religion between dissemination efforts by experts from above and the self-empowerment of lay people from below.’ - Jan Stievermann, Heidelberg University, Germany. This open access book focuses on the potential for conflict between high and low culture during the transformations of the popular in the field of religion in the nineteenth and early twentieth centuries. Specifically, the contributors to this edited collection consider the so-called 'Revival Movements' that came up as a symptom of differentiation and pluralisation of Protestantism in reaction to the Enlightenment, rationalism, and criticism of religion, and explore the attempts at theological self-empowerment of Christian laymen and laywomen. Veronika Albrecht-Birkner is University Professor in Church and Theology History at the University of Siegen, Germany. Stefanie Siedek-Strunk is Research Assistant at the CRC 1472 ‘Transformations of the popular’ at the University of Siegen, Germany.